Structural diversification and neo-functionalization during floral MADS-box gene evolution by C-terminal frameshift mutations - Vandenbussche, Michiel (Oxford University Press, 2003)
Frameshift mutations generally result in loss-of-function changes since they drastically alter the protein sequence downstream of the frameshift site, besides creating premature stop codons. Here we present data suggesting that frameshift mutations in the C-terminal domain of specific ancestral MADS-box genes may have contributed to the structural and functional divergence of the MADS-box gene family. We have identified putative frameshift mutations in the conserved C-terminal motifs of the B-function DEF/AP3 subfamily, the A-function SQUA/AP1 subfamily and the E-function AGL2 subfamily, which are all involved in the specification of organ identity during flower development. The newly evolved C-terminal motifs are highly conserved, suggesting a de novo generation of functionality. Interestingly, since the new C-terminal motifs in the A- and B-function subfamilies are only found in higher eudicotyledonous flowering plants, the emergence of these two C-terminal changes coincides with the origin of a highly standardized floral structure. We speculate that the frameshift mutations described here are examples of co-evolution of the different components of a single transcription factor complex. 3′ terminal frameshift mutations might provide an important but so far unrecognized mechanism to generate novel functional C-terminal motifs instrumental to the functional diversification of transcription factor families.